2023
DOI: 10.1111/rda.14368
|View full text |Cite
|
Sign up to set email alerts
|

Economics of treatment with GnRH agonist 7–14 days after artificial insemination in repeat breeder lactating dairy cows

Abstract: This study looked at the effectiveness and financial benefits of treating repeat breeder (RB) dairy cows with the GnRH agonist gonadorelin 7–14 days after artificial insemination (AI). A total of 188 healthy dairy cows (2.4 ± 1.3 lactations) with an average milk yield of 42.1 ± 6.8 kg milk/day, at 179 ± 38.4 days in milk with 3.8 ± 1 AIs were divided into two groups, experimental (E group, n = 98) and control (C group, n = 90). The GnRH agonist gonadorelin was given 7–14 days after AI to the E group to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…However, when we evaluated the pregnancy rates and conception rates based on the number of AIs, the G5 group showed an improvement in reproductive activity for nulliparous dairy cows at 2 and +4 AIs and for the repeat breeder dairy cows at +3 lactations. This is consistent with our previous study [1], which showed that administering this therapy 7-14 days after AI improved reproductive activity in repeat breeder cows. This finding indicates that administering gonadorelin during earlier and latter in the luteal phase may increase the survival of embryos in repeat breeders heifers and dairy cows.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, when we evaluated the pregnancy rates and conception rates based on the number of AIs, the G5 group showed an improvement in reproductive activity for nulliparous dairy cows at 2 and +4 AIs and for the repeat breeder dairy cows at +3 lactations. This is consistent with our previous study [1], which showed that administering this therapy 7-14 days after AI improved reproductive activity in repeat breeder cows. This finding indicates that administering gonadorelin during earlier and latter in the luteal phase may increase the survival of embryos in repeat breeders heifers and dairy cows.…”
Section: Discussionsupporting
confidence: 93%
“…However, the data on the effectiveness of the treatment and the impact of aCL on reproductive performance are not consistent. In our previous study, we confirmed that administering GnRH between 7-14 days after artificial insemination (AI) can increase the number of aCL and improve reproductive performance in repeat-breeder dairy cows [1]. According to the results of Doležel et al, [17], inducing aCL through gonadorelin administration was found to be more efficient in cows treated on day 5 following insemination, as compared to cows treated on days 6 or 7.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It has been found that GnRH administration during the diestrous phase (5–7 days post AI) can increase the proportion of cows with an additional CL, which enhances embryo survival [ 54 ]. Similar results were observed when GnRH was administered between the 7th and 14th days after AI in dairy cows [ 55 ] and lactating buffaloes [ 56 ]. Previous research suggested that GnRH administration on day 12 of the previous cycle improves ovulation and conception rates compared to the control group, and it significantly increases P 4 concentrations in pregnant cows on day 22 [ 57 ].…”
Section: Prevention Of Pregnancy Losses By Gnrh Treatmentsupporting
confidence: 81%
“…A double dose (250 µg) increased the pregnancy rate and suggested that it could improve embryo survival. There is evidence that the administration of GnRH agonists in RBCs between 7 and 14 days after AI stimulates the development of a second CL and promotes embryo survival, resulting in a significant increase in pregnancy rate (11 percentage points compared to the control group) [ 120 ].…”
Section: Therapeutic Control Of the Estrous Cyclementioning
confidence: 99%